Upaya Meningkatkan Hasil Belajar Materi Geometri Melalui Media Gambar Siswa Kelas I pada Sekolah SDN Pematang Buluh Kecamatang Secanggang Kabupaten Langkat - Ramadhan, M.; Dwi, Dara Fitrah; Napitupulu, Safrida; Silalahi, Beta Rapita (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Efforts to develop the education sector in Langkat Regency continue to be carried out both by providing/improving physical educational facilities as well as civil servant teachers and honorary teachers which aim to increase school participation at every level of education and quality/quality. The learning media that will be applied at the elementary school level must be a medium that is easy to use and accepted by students. Image media can serve as a learning tool designed by teachers themselves to increase effectiveness and efficiency in education. Picture media in math education can help students understand concepts, improve clarity in learning, and engage students in the classroom. Students tend to be passive during the learning process if the infrastructure used in teaching and learning activities is less supportive. Efforts to overcome this, the appropriate and varied use of learning media can help overcome students' passive attitudes in participating in teaching and learning activities. The use of image media in the teaching and learning process is said to channel messages, relate to real life with the material taught can be helped by image media as an intermediary. This research will be carried out at SDN 050660 Pematang Buluh, Secanggang District, Langkat Regency. The time for this research is carried out from August to December 2024 for the 2024/2025 Academic Year. The method used by the researcher is a qualitative method. As for the description of the results of this study, the researcher uses a descriptive method, which is a method that aims to describe the nature of something that is going on at the time the research is conducted. Research Cycle Design. This can be seen from the results of the preliminary test which stated that only 3 students or 9% were declared complete, while 29 students or 91% were declared incomplete. Based on the results of the post-test in cycle I and cycle II, namely: from 32 students, based on the results of the post-test in cycle I, it can be seen that 18 students or 56.25% were declared to have completed their studies, while 14 students or 43.75% were declared to be incomplete in learning and cycle II it is known that 31 students or 99% were declared complete in learning, Meanwhile, 1 student or 3% was declared to be still incomplete in learning.